2018
DOI: 10.1002/ecm.1332
|View full text |Cite
|
Sign up to set email alerts
|

Pace of life syndrome under warming and pollution: integrating life history, behavior, and physiology across latitudes

Abstract: To fully comprehend and predict the impact of drivers of global change such as climate warming and pollution, integrated multi‐trait approaches are needed. As organismal traits are often correlated, responses to stressors are expected to induce coordinated changes in many traits. A promising framework to study this is the pace of life syndrome (POLS), which predicts the integration of life history, behavioral, and physiological traits along a fast‐slow continuum. Using an integrative multi‐trait approach, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 156 publications
8
85
3
Order By: Relevance
“…The study species shows striking latitudinal differences in life history, with higher larval growth rates in the multivoltine (3–4 generations per year), low‐latitude populations compared to the semivoltine (2 years per generation), high‐latitude populations (Stoks and De Block , Shama et al , Stoks et al , Debecker et al , Debecker and Stoks , Van Dievel et al , Verheyen and Stoks ). Moreover, we have recently shown in separate studies that the low‐latitude populations of the species have a longer adult lifespan (reported as Supporting Information in Debecker et al ) and higher levels of antioxidant enzymes in the larval stage (Debecker and Stoks ). Building on these previous findings, the current study aims to elucidate the mechanism underpinning this atypical fast growth – long lifespan pattern in terms of oxidative stress physiology.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The study species shows striking latitudinal differences in life history, with higher larval growth rates in the multivoltine (3–4 generations per year), low‐latitude populations compared to the semivoltine (2 years per generation), high‐latitude populations (Stoks and De Block , Shama et al , Stoks et al , Debecker et al , Debecker and Stoks , Van Dievel et al , Verheyen and Stoks ). Moreover, we have recently shown in separate studies that the low‐latitude populations of the species have a longer adult lifespan (reported as Supporting Information in Debecker et al ) and higher levels of antioxidant enzymes in the larval stage (Debecker and Stoks ). Building on these previous findings, the current study aims to elucidate the mechanism underpinning this atypical fast growth – long lifespan pattern in terms of oxidative stress physiology.…”
Section: Introductionmentioning
confidence: 89%
“…Mated females were collected in the field from two populations in southern Sweden (Genarp 55°36′N, 13°23′E and Vallby 55°38′N, 13°17′E) where the species is semivoltine, and from two populations in southern France (St‐Martin De Crau 43°37′N, 4°46′E and Salin de Giraud 43°24′N, 4°43′E) where the species has 3–4 generations per year (Corbet et al ). Ponds in these regions do not show latitudinal differentiation in several abiotic (pH, oxygen levels) and biotic variables (chlorophyll a levels, densities of fish and macroinvertebrate predators) (Debecker and Stoks ). Mean summer water temperatures in these ponds are ~24°C in southern France and ~20°C in southern Sweden (Debecker and Stoks ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global environmental changes are altering the habitats of many species (Peñuelas et al, 2013). For 30 species with wide geographic ranges, intra-specific variation in life-history strategies resulting from 31 historical selection might predispose some populations to be more or less susceptible to increasing 32 environmental changes (Candolin, 2019;Debecker and Stoks, 2019;Harding et al, 2019). Environmental 33 variation favors individuals that differentially allocate time and energy to reproduction and self-34 maintenance in order to maximize lifetime fitness (Stearns, 1989;Stearns, 1992;Ricklefs and Wikelski, 35 2002).…”
Section: Introduction 29mentioning
confidence: 99%